Echoes Of Care: A Nurse-Led Journey into the Sleep and Emotional Realms of Hospitalized Children - Ashalin Raja Brintha Palas; Shankar Shanmugam Rajendran; Kannan Kasinathan; Shanmugapriya Shanmugasundharam; Nathiya Balasubramaniyan; Abisha Mary Antony Johnson Kennady; Dr. Winston Thomas (The Bioscan, 2025)
Background: Hospitalization can significantly impact children's sleep patterns and emotional well-being. This study aimed to evaluate the effectiveness of nurse-led interventions in reducing sleep disturbances and emotional distress among hospitalized children, and to explore mothers' perceptions of the paediatric inpatient experience. Methods: A sequential explanatory mixed-methods design was employed. The quantitative phase involved a pre-experimental one-group pre-test and post-test study with 100 hospitalized children aged 3-6 years. The qualitative phase included interviews with six mothers. Data were collected using the Children's Sleep Habits Questionnaire and Paediatric Emotional Distress Scale. Nurse-led interventions focused on creating sleep-friendly environments, establishing bedtime routines, and providing emotional support. Results: Following the intervention, 80% of children exhibited mild sleep disturbances, while 20% achieved normal sleep patterns. Emotional distress levels reduced significantly, with 73% experiencing mild distress and 27% showing normal/low distress. A strong negative correlation (r = -0.682) was found between improved sleep and reduced emotional distress. Qualitative analysis revealed themes related to sleep routine changes, environmental impacts, and coping strategies. Conclusion: Nurse-led interventions significantly improved sleep quality and reduced emotional distress in hospitalized children. The study highlights the importance of holistic, family-centered care in paediatric settings.